Negotiation of identity and internal contradictions: The Terengganu and Kelantan Peranakan Chinese foodways compared - Tan, Yao Sua; Ngah, Kamarudin; Lim Abdullah, Mohd Shahrul Imran (Taylor & Francis Group, 2015)
This study explores the Terengganu and Kelantan Peranakan Chinese foodways with special reference to two types of foods: daily and ancestral prayer foods.The principal focus is to illustrate the negotiation of identity through foodways as well as internal contradictions arising from this process of identity negotiation.These two groups of Peranakan Chinese are largely the product of acculturation by the local Malays through socio-cultural interactions, though the Kelantan Peranakan Chinese are also acculturated by the local Thai community.Their daily and ancestral prayer foods display contrasting identities that stem from the negotiating of their acculturated and primordial identities.The former displays a strong local cultural influence, while the latter displays a strong Chinese cultural influence. However, despite the pervasive influence of localisation in their daily foods, elements of hybridisation are visible in some occasionally prepared food items.Meanwhile, localised and hybrid food items are included in their ancestral prayer foods, which are supposed to express their primordial Chinese identity.These internal contractions illustrate the complexity of the negotiation of identity through foodways within a cross-cultural context.